Academic buoyancy and academic engagement in English speaking learning among Chinese college students: the mediation of enjoyment and the moderation of anxiety - Zhao, Yurong; Huang, Xiaowei; Hui, Lianghong (Frontiers in Psychology, 2025)
BackgroundLearners' academic engagement in English speaking learning is crucial for improving their English speaking abilities through the process of motivation. Although prior research has explored predictors of EFL (English as a Foreign Language) academic engagement, such as academic buoyancy and foreign language learning emotions, the underlying mechanisms among these variables remain largely unexplored, especially in college English speaking learning. Given this, elucidating these mechanisms is essential for advancing the understanding of how to effectively promote English speaking proficiency among college students.PurposeThis study aims to construct a structural equation model (SEM) with a sample of 244 college students from two highly-ranked Chinese universities to examine the mediating role of foreign language enjoyment and the moderating effect of foreign language anxiety in the relationship between academic buoyancy and academic engagement within the context of Chinese college English speaking learning.MethodsBased on a correlation design, data from 244 Chinese EFL college students were collected via an online questionnaire in December 2023 and analyzed through a moderated mediation model with SPSS 26.0, IBM Amos 22, Mplus 8.3, and PROCESS v4.2, applying 2,000 bootstrap iterations.ResultsThe results reveal that English speaking learning buoyancy (ESLB) positively predicted English speaking learning engagement (ESLEG) both directly and indirectly through the mediating role of English speaking learning enjoyment (ESLE). Additionally, English speaking learning anxiety (ESLA) significantly and negatively moderated the relationships between ESLB and ESLE, as well as between ESLB and ESLEG.ConclusionThese findings highlight the complex interactions of academic buoyancy and foreign language learning emotions on engagement in English speaking learning. The study provides valuable pedagogical implications for enhancing English speaking instruction in Chinese colleges.